2016
DOI: 10.1016/j.niox.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial AMPK activation induces mitochondrial biogenesis and stress adaptation via eNOS-dependent mTORC1 signaling

Abstract: Metabolic stress sensors like AMP-activated protein kinase (AMPK) are known to confer stress adaptation and promote longevity in lower organisms. This study demonstrates that activating the metabolic stress sensor AMP-activated protein kinase (AMPK) in endothelial cells helps maintain normal cellular function by promoting mitochondrial biogenesis and stress adaptation. To better define the mechanisms whereby AMPK promotes endothelial stress resistance, we used 5-aminoimidazole-4-carboxamide riboside (AICAR) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 46 publications
(59 reference statements)
0
23
0
Order By: Relevance
“…It also activates AMP-activated kinase (AMPK), which promotes insulin sensitivity by inhibiting PKC isoforms and the associated NF- κ B activation, oxidative stress, ER stress, and apoptosis [ 284 291 ]. AMPK also induces mitochondrial biogenesis, which limits endothelial cell dysfunction, for example, in response to angiotensin II signaling [ 292 ]. Phosphorylation of SIRT1 by JNK1 primes SIRT1 for ubiquitination and degradation, and persistent JNK1 activation in obesity causes severe hepatic SIRT1 degradation [ 293 ].…”
Section: Inhibition Of Insulin Signaling By Cellular Stress Responmentioning
confidence: 99%
“…It also activates AMP-activated kinase (AMPK), which promotes insulin sensitivity by inhibiting PKC isoforms and the associated NF- κ B activation, oxidative stress, ER stress, and apoptosis [ 284 291 ]. AMPK also induces mitochondrial biogenesis, which limits endothelial cell dysfunction, for example, in response to angiotensin II signaling [ 292 ]. Phosphorylation of SIRT1 by JNK1 primes SIRT1 for ubiquitination and degradation, and persistent JNK1 activation in obesity causes severe hepatic SIRT1 degradation [ 293 ].…”
Section: Inhibition Of Insulin Signaling By Cellular Stress Responmentioning
confidence: 99%
“…AMPK is activated in response to an increase in the intracellular (AMP + ADP):ATP ratio and simultaneous AMPKα Thr172 phosphorylation by the upstream kinases liver kinase B1 or calcium/calmodulin-dependent protein kinase kinase β [9,10]. Activated AMPK inhibits anabolic processes which consume ATP [9,10], reduces inflammation [11,12], inhibits endothelial cell proliferation [13], stimulates mitochondrial biogenesis [14], and increases insulin sensitivity [9,15], making it an attractive pharmacological target for diabetes and cardiovascular pathologies [10]. There are 12 differentially expressed AMPK isoforms, each composed of catalytic α1/α2, and regulatory β1/β2 and γ1/γ2/γ3 subunits [9,10], allowing a specialised cellular and systemic response to different metabolic stimuli [10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that AMPK activation improved insulin sensitivity and energy homeostasis, and attenuated inflammatory signalling in insulin-sensitive tissues, such as muscle [14], liver [16,17] and adipose tissue [11,18] as well as ECs [12,15]. Several AMPK activators have been shown to increase NO synthesis in HAECs in an AMPK-dependent manner [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in humans have demonstrated that JNK activation is associated with endothelial dysfunction as assessed by flow-mediated dilation (an established measure of endothelial function) [91]. Both cytokines and ROS activate JNK signaling and cause endothelial dysfunction [92], apoptosis, and endothelial ‘activation’ which promotes monocyte adhesion in areas susceptible to atherosclerotic plaque formation. With endothelial health in mind, the importance of JNK1 deletion was investigated in the LDL receptor knockout (LDLR −/− ) model of atherosclerosis [42].…”
Section: Jnk In Atherosclerosis: Complicated Biology and Divergent Exmentioning
confidence: 99%